2016
DOI: 10.1111/1745-9133.12248
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Findings from the HOPE Demonstration Field Experiment

Abstract: P e n n s y l v a n i a S t a t e U n i v e r s i t y Debbie Dawes R T I I n t e r n a t i o n a l Elaine Arsenault P e n n s y l v a n i a S t a t e U n i v e r s i t yStephen Tueller R T I I n t e r n a t i o n a l Research SummaryMore than 1,500 probationers in four sites were randomly assigned to probation as usual (PAU) or to Honest Opportunity Probation with Enforcement (HOPE), which is modeled on Hawaii's Opportunity Probation with Enforcement (Hawaii HOPE) program that emphasizes close monitoring; fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 47 publications
0
45
0
Order By: Relevance
“…SCF, however, cannot be justified on other grounds as has been done, for example, by Kleiman, Hawken, and Halperin (). Or, as Lattimore and colleagues (: 29) have noted:
In many ways, HOPE/SCF probation is what many citizens envision as probation as usual—i.e., that individuals on community supervision are subject to a set of conditions to which they are expected to adhere. Failure to adhere to these conditions results in a response.
…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SCF, however, cannot be justified on other grounds as has been done, for example, by Kleiman, Hawken, and Halperin (). Or, as Lattimore and colleagues (: 29) have noted:
In many ways, HOPE/SCF probation is what many citizens envision as probation as usual—i.e., that individuals on community supervision are subject to a set of conditions to which they are expected to adhere. Failure to adhere to these conditions results in a response.
…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as pointed out by Lattimore et al. () and Drake (), both the effectiveness of an experimental intervention and any attendant cost savings are reflective not only of the intervention but also of the “compared to what”—the control or comparison condition. The DFE was characterized by both small variations in HOPE implementation across the sites and significant variation in PAU (see Lattimore et al., ).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…That is precisely the investigation that Alexander Cowell, Alan Barnosky, Pamela Lattimore, Joel Cartwright, and Matthew DeMichele (: 875–899) undertook, using a sample from the well‐regarded multisite demonstration field experiment, the Honest Opportunity Probation Enforcement program (HOPE DFE). The randomized controlled trial results showed no differences in recidivism for HOPE DFE participants compared with those in probation as usual (Lattimore, MacKenzie, Zajac, Dawes, Arsenault, and Tueller, ), and the findings from the benefit–cost analysis demonstrated no achieved criminal justice cost‐savings at three HOPE DFE sites, as well as a statistically significant increase in costs at one HOPE DFE site in the long‐run follow‐up. In her policy essay response to Cowell et al.…”
mentioning
confidence: 92%
“…Interestingly, Lattimore et al. () and others have noted that some view SCF as what community supervision “should be” or “believe it to be” (Bartels, ; Lattimore et al., ). The TAU problem (Burns, ) has serious policy consequences by way of rejecting potentially effective programs like SCF (Hawken, ; Kleiman, ).…”
mentioning
confidence: 99%